SOCIO-MEDIO-ETHICAL PERISCOPE OF FASTING AND PRAYER IN HEALINGSYNDROME IN CHRISTIAN FAITH - Adesanwo, Emmanuel Remi (Religions' educator, 2018)
This paper is geared towards examining fasting and prayer that cuts across religious and mystical movements and cultures. The Christian believers indireneedhaveresortedtoanythinginthenameofprayerandfastingasasolutiontoproblems.Consequently,scholars have either ignore the dangerorchallengesthatassociatedwithexcruciatingpainsinthespiritualexercise. Basicideassuchashomeostasis of the body, nutritional elements and processesareillustratedinthisworkconcerningtheeffectsofthedisturbedfoodandfluidintakeintothebody.There are clinicalperiscopes of the break-down of the body’sregulatorymechanisms.Thesocio-medicaleffectsoflackofcertainessentialsnutrientsmanifestonthebodyandthebraininpersistenceprolongedfastingandprayerinChristianfaith.Thispaperwilldiscussonsocio-medio-ethicalaspectonthesubjectmatter.Thenatureofthisresearchcallsforexperientialobservation,documentaryandhistoricalanalysesofliterarysources.Acombinationofthesemethodsisveryuseful for data collection.